If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15k + -7k + -10 = 12 Reorder the terms: -10 + -15k + -7k = 12 Combine like terms: -15k + -7k = -22k -10 + -22k = 12 Solving -10 + -22k = 12 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + -22k = 12 + 10 Combine like terms: -10 + 10 = 0 0 + -22k = 12 + 10 -22k = 12 + 10 Combine like terms: 12 + 10 = 22 -22k = 22 Divide each side by '-22'. k = -1 Simplifying k = -1
| 1/38=2.25/x | | 7/3-7i | | 5x-31=x+5 | | 9x+27x^2= | | -12n+16n+-19=-13 | | -3a+8b+61=0 | | 27.00/2.25 | | 1/38=5.5/x | | 2(c-8)+-6=8 | | -2x+3(x-3)=-13 | | 11=-5x+21 | | a^4+8=11 | | 6-7x=5x-10x+8 | | 3x+4=-39 | | 10=2(c+1)+2 | | 7(3x-2)=5(2x-1) | | 24x-3(8x-18)=54 | | 6x+2(2x-3)=24 | | 7p-6p=-11 | | Y=0.25x^2+10x+80 | | 3x^(-1/2)=8 | | 12-v=9 | | 4x+5x-34=68-8x | | 3x^(-1/2)-8=0 | | (a*a)-5a+25+(b*b)+6b+36=0 | | -6=3(x-19) | | 4x+x-15+x-4=180 | | 6-2x=6x-10x-16 | | 5b+6b-9b+1=7 | | 2(1-2a)=7(a-6) | | 2(x-3)-3=3 | | 11=4(n-17)+15 |